Detection and knockdown of MicroRNA-34a using thioacetamido nucleic acid - Soni, Kartik; Gupta, Shivani; Gokhale, Sachin S.; Dey, Rakesh; Gunjal, Anita D.; Kumar, Vaijayanti A.; Pillai, Beena (Nucleic Acid Therapeutics, 2013)
Thioacetamido nucleic acids (TANA) contain a backbone modification of dinucleotides consisting of a 5-atom amide linker N3'-COCH2-S-CH2 at thymidine or thymidine-cytidine dimer blocks. Here, the chemical synthesis of the TANA linked 5-methyl-cytidine-cytidine ((Me)cc) dimer block and its incorporation into the DNA sequence, complementary to human microRNA 34 (miR-34) is described. Further, for the first time, we demonstrate the biological applications of TANA modified oligonucleotides in detection and intracellular knockdown of a cancer related microRNA in comparison with DNA containing locked nucleic acid (LNA) and 2'-O-methyl modifications. The human microRNA miR-34 is a pro-apoptotic microRNA under the transcriptional control of protein 53 (p53). It gets expressed in response to DNA damage and regulates several cell cycle and apoptosis related targets. Here, we show that the TANA modified antisense oligonucleotide binds specifically to miR-34a, allowing its detection using primer extension. We also show that, using the TANA modified antisense oligonucleotide against miR-34a, intracellular levels of miR-34 can be reduced, and consequently, the expression of its target oncogene V-myc myelocytomatosis viral related oncogene, neuroblastoma derived (MYCN) is enhanced. Further, we assessed the toxicity and serum stability of the oligonucleotide to conclude that it is suitable for detection and modulation of the vital biomarker and tumor suppressor microRNA.